2017
DOI: 10.3892/mmr.2017.6744
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of PPAR-γ and TRPC in neonatal rats with persistent pulmonary hypertension

Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is a life-threatening disease that is commonly observed in the neonatal intensive care unit. PPHN is pathologically characterized by pulmonary vascular remodeling and, in particular, pulmonary artery smooth muscle cell (PASMC) proliferation. Decreased expression levels of peroxisome proliferator-activated receptor γ (PPAR-γ), which is a member of the nuclear receptor hormone superfamily, in combination with elevated expressions of transient receptor poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…PPAR-γ is a member of the nuclear receptor hormone super family, and it is downregulated through TGF-β1 signaling in PASMC, whereas TRPC1 and 6 are upregulated in neonatal and adult rodents with hypoxic pulmonary hypertension. Conversely, stimulation of PPAR-γ reverses pulmonary hypertension and remodeling, and down regulates SOC expression ( Gong et al, 2011 ; Yang et al, 2015 ; Jiang et al, 2016 ; Du et al, 2017 ).…”
Section: Trp Stim Orai and Asic Proteins: Tension Development And mentioning
confidence: 99%
“…PPAR-γ is a member of the nuclear receptor hormone super family, and it is downregulated through TGF-β1 signaling in PASMC, whereas TRPC1 and 6 are upregulated in neonatal and adult rodents with hypoxic pulmonary hypertension. Conversely, stimulation of PPAR-γ reverses pulmonary hypertension and remodeling, and down regulates SOC expression ( Gong et al, 2011 ; Yang et al, 2015 ; Jiang et al, 2016 ; Du et al, 2017 ).…”
Section: Trp Stim Orai and Asic Proteins: Tension Development And mentioning
confidence: 99%
“…Researchers revealed that these expressions were observed in the cytoplasm of PASMCs and the expression of both proteins was greatly increased in the PAH group as compared with the rats in the CON group. [ 59 ] In the Western blot analysis performed in the same study, they also found that TRPC1 and TRPC6 protein expression was significantly increased as compared with the CON group. [ 59 ] HX selectively causes increased expression of TRPC1 and TRPC6 in mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 92%
“…[ 59 ] In the Western blot analysis performed in the same study, they also found that TRPC1 and TRPC6 protein expression was significantly increased as compared with the CON group. [ 59 ] HX selectively causes increased expression of TRPC1 and TRPC6 in mRNA and protein levels. [ 60 ] Zhang et al [ 61 ] found significant increases in the level of mRNA in the hypoxic group in the PAH model that they created with chronic HX.…”
Section: Discussionmentioning
confidence: 95%
“…Berger et al (19) suggested that the BNP expression level in the plasma of patients with heart failure is significantly higher than that in the normal individuals, which is important for diagnosing and classifying heart failure. Du et al (20) also proposed that the BNP expression level in patients with PIH is significantly increased, with a diagnostic value. In the historical literature search, there are few studies on the correlation of miR-21 and BNP with PIH complicated with heart failure and their diagnostic values, which were detected and analyzed in the present study for clarification.…”
Section: Discussionmentioning
confidence: 99%